2008
DOI: 10.1093/cvr/cvp054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contractile mechanisms of sphingosylphosphorylcholine and sphingosine-1-phosphate in rabbit coronary artery

Abstract: Our results suggest that constriction of coronary arteries in response to the bioactive lipid S1P or SPC occurs by distinct signalling pathways. Activation of the RhoA/RhoA-associated kinase pathway and subsequent phosphorylation of MYPT1 play a key role in SPC-induced coronary contraction, whereas elevation of [Ca2+]i is crucial for S1P-induced coronary constriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…Our results also show that afferent arterioles are highly sensitive to S1P compared with the resistance vessels from other vascular beds. [27][28][29] Importantly, in contrast with the effect of S1P in preglomerular microvessels, we found efferent arterioles to be completely unresponsive to S1P. Despite the lack of an efferent arteriole response to S1P, NE vasoconstricted those same efferent arterioles as reported earlier, 35 indicating that these arterioles were capable of responding to vasoconstrictor signals but just were not responsive to S1P.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results also show that afferent arterioles are highly sensitive to S1P compared with the resistance vessels from other vascular beds. [27][28][29] Importantly, in contrast with the effect of S1P in preglomerular microvessels, we found efferent arterioles to be completely unresponsive to S1P. Despite the lack of an efferent arteriole response to S1P, NE vasoconstricted those same efferent arterioles as reported earlier, 35 indicating that these arterioles were capable of responding to vasoconstrictor signals but just were not responsive to S1P.…”
Section: Discussionsupporting
confidence: 57%
“…1,2,5 Recent studies indicate that S1P plays an important role in regulating vascular tone in resistance vessels, including cerebral, coronary, and mesenteric arteries 16,[27][28][29][30][31][32] ; however, very little is known about the renal influence of S1P under either physiologic or pathophysiologic conditions. Bischoff et al reported that S1P vasoconstricted isolated intrarenal arteries 14 and reduced RBF without changing arterial pressure in anesthetized rats, 15 indicating that S1P may be an important regulator of renal vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). S1P enhances Ca 2+ mobilization (101)(102)(103)(104)(105) and stimulates the ERK/MAPK pathway to promote cell growth and survival ( 95 ). It may also activate the PI3K/Akt pathway ( 106 ) to affect the balance between pro-and anti-apoptotic Bcl-2 proteins ( 95, 107 ) and activator protein 1 and NF-B, which promote survival ( 108 ).…”
Section: Sphingolipids In the Eyementioning
confidence: 99%
“…Sphingosylphosphorylcholine (SPC), a biologically active sphingomyelin metabolite, aug- mented contractile force at pCa 6.3 in β-escin-permeabilized rabbit coronary arteries [12]; a muscarinic agonist induces calcium sensitization in β-escin-permeabilized rat and guinea-pig detrusor smooth muscles [13]; histamine, ET-1 and PDBu induce calcium sensitization in α-toxin-permeabilized rabbit femoral artery [14]; a thromboxane A2 agonist, U46619-induced contraction involves Ca 2+ entry and calcium sensitization in rat caudal arterial smooth muscle [15]. However, whether NaF induces calcium sensitization is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The relaxing solution containing (in mM) potassium methanesulfonate, 74.1; MgATP, 4.5; EGTA, 1.0; PIPES, 30, and creatine phosphate, 10 were neutralized to pH 7.4 with KOH at 25 o C as previously described [12]. The free Ca 2+ concentration was calculated using a computer program and expressed as the negative logarithm (pCa).…”
Section: Permeabilization and Tension Recordingmentioning
confidence: 99%